Berat Badan dan Panjang Badan Lahir Meningkatkan Kejadian Stunting - Sutrio Sutrio; Mindo Lupiana (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2019)
Background: Stunting is still a public health problem. The prevalence of stunting in Lampung Province ranks sixth in Indonesia (42.6%). Stunting prevalence based on Nutrition Status Monitoring in 2016 in Pesawaran Regency ranks number four (35.1%). Nutrition student data collection results in Cipadang Village, 12 stunting toddlers (34.3%). Purpose: The study aims to determine the relationship between body weight and birth length with the incidence of stunting in toddlers. Methods: An analytical cross sectional research design was conducted in Cipadang Village, Gedong Tataan Subdistrict, Pesawaran District in 2018. The population was all children under five in the study area with a total sample of 103 people taken by random sampling technique. Data collection was carried out by interview and observation to obtain data on the research variables analyzed, including the incidence of stunting, birth weight and birth length. Data analysis with univariate and bivariate analysis using chi square test. Results: The results showed the prevalence of stunting was 34.9%, LBW 24.3% and low birth length 31.1%. There is a relationship between birth length and birth weight with toddler stunting. Conclusion: Birth weight and birth weight are risk factors for increasing stunting. Increased monitoring of toddler growth on a regular basis in the Posyandu and prevention of LBW should be done to prevent stunting.